EVALUATING THE EFFICACY OF T. AFRICANA EXTRACTS COMBINED WITH CONVENTIONAL ANTIBIOTICS AGAINST MULTIDRUG-RESISTANT PATHOGENS (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
The global rise of multidrug-resistant (MDR) pathogens threatens the efficacy of conventional antibiotics, necessitating novel therapeutic strategies. This study evaluates the efficacy of Terminalia africana (T. africana) methanolic extracts combined with antibiotics (ampicillin, ciprofloxacin, ceftriaxone) against MDR Escherichia coli, Klebsiella pneumoniae, and Staphylococcus aureus (MRSA). Grounded in the multi-target hypothesis, which posits that plant extracts enhance antibiotic action by targeting multiple bacterial sites, we employed a primary experimental design. In vitro assays, including minimum inhibitory concentration (MIC) determination, checkerboard synergy testing, and time-kill kinetics, were conducted using clinical isolates from Lagos, Nigeria. T. africana extracts alone exhibited MICs of 64–256 µg/mL, while combinations with antibiotics reduced MICs by up to 4-fold. Checkerboard assays revealed synergy (fractional inhibitory concentration index, FICI ≤ 0.5) in 70% of combinations, notably with ampicillin and ciprofloxacin, reducing bacterial viability by 3-log10 within 12 hours in time-kill assays (p < 0.01). Ceftriaxone combinations showed indifference (FICI 0.75–1.25), possibly due to β-lactamase resistance. These findings suggest that T. africana extracts disrupt resistance mechanisms, enhancing antibiotic potency. The study underscores the potential of plant-based adjuvants in combating AMR, particularly in resource-limited settings. We recommend in vivo validation and phytochemical characterization to advance clinical applications.